تأثير بعض الأوساط الزراعية العضوية على إنبات بذور ونمو بادرات ثلاثة أنواع حراجيّة وآخر رعوي و تحديد محتواها الغذائي - صالح, أمين; علاء الدين, حسن; كبيبو, عيسى (Latakia University Journal -Biological Sciences Series, 2019)
يهدف البحث إلى دراسة تأثير إضافة أنواع مختلفة من الفضلات الزراعية العضوية ( تفل – عرجوم – نجارة ) بعد معالجتها بالتخمير إلى الخلطة التقليدية المستخدمة في المشاتل الحراجية والمكونة من تربة ورمل بنسبة (1:1) وتفل الملك(المسوق تجارياً)، وذلك على بعض الخصائص الإنباتية لبذور ثلاث نباتات حراجية (الصنوبر الكناري، السرو دائم الاخضرار ،الكستناء) ونبات رعوي (الروثة) ومستويات النمو المختلفة والمحتوى الغذائي. أظهرت الدراسة أن تأثير وسط النمو على إنبات البذور اختلف بحسب نوع النبات ، حيث اختلفت استجابة بذور الأنواع الأربعة لأوساط النمو وخلائطها بشكل واضح ، كما أظهر كلٌ من وسط العرجوم ووسط العرجوم مع خلطة المشتل تفوقاً واضحاً في أغلب الخصائص الإنباتية ومستويات النمّو في الأنواع المدروسة وخصوصاً عند الروثة . This research aims at studying the effect of additions of different organic agricultural wastes (olive cake, dried olive cake, chaving) after treatment by fermentation of the traditional nursery mix that consists of soil and sand (1:1). Another objective of the study is to investigate the effect of olive cake substrate (trademark The King) on the germination properties of the seeds of three forest species (Pinus canariensis, Cupressus sempervirens and Castania sativa) and a pastoral plant species (Salasola vermiculata), and the effects on growth and nutritional contents. This study shows that the effects of growth ambiance on seed germination are influenced by the species and the interaction between plant species and substrates, and the effect has been significant. Both the dried olive cake substrate, "traditional nursery, dried olive cake substrate mix" are better in terms of most germination properties and levels of growth in the plant species at issue, especially S. vermiculata.